Effect of Nasoalveolar Molding on Nasal Symmetry in Patients With Cleft Lip and Palate: A Systematic Review - Parastoo Namdar; Farzaneh Lal Alizadeh; Tahura Etezadi; Leily Sadri; Atena Shiva (Mazandaran University of Medical Sciences, 2020)
Context: One of the main types of nasal deformity is the unilateral cleft lip or palate, which affects breathing and smelling. It is supposed that nasoalveolar molding (NAM) has a positive effect on the reduction of the tension in lips and helps to simplify or even eliminate the subsequent orthodontic treatment. Objective: This systematic review of papers focused on the effectiveness of NAM in patients with unilateral cleft lip or palate. Data Sources: The databases of Google Scholar, PubMed, Web of Science, and Medline were searched. Study Selection: A total of 1282 relevant articles published up to 2018 were identified. The selected papers were screened based on the eligibility criteria after the thorough investigation of their titles and abstracts. In the next step, the inconsistent articles with our objectives were removed. Afterward, the papers were thoroughly studied, and data related to our study goals were extracted and recorded in predetermined extraction forms. After the full-text evaluation of the articles, 22 articles were finally selected. Data Extraction: The search process was performed with the following keywords in combination with nasoalveolar molding or pre-surgical nasoalveolar molding or pre-surgical orthopedic appliances: "unilateral cleft lip or palate", "UCL/P", "Cleft lip", "Cleft palate".  Results: Based on the literature, many studies have supported the effectiveness of NAM appliance therapy on nasal symmetry in the unilateral cleft of the lip and or palate treatment. Conclusions: The NAM therapy is effective in decreasing the severity of the initial cleft deformity, as well as repositioning of deformed nasal cartilage and alveolar process. It has many beneficial results in surgical outcomes. However, the long-term effect of this approach has remained unclear.